Hybrid split Pi converter - Khan S.A.; Pilli N.K.; Singh S.K. (My University, 2025)
This paper brings forward a hybrid converter derived from the Split-Pi converter, which can provide simultaneous ac as well as dc outputs from the same dc input. The proposed converter can work both as a step up and step down converter, whereas most of the available hybrid topologies work in step up mode only. The inbuilt property of shoot through protection in inversion stage, makes this converter prone free to the distortion in output caused by the inadequate dead time and thereby improving the reliability of the converter. The proposed converter fits best in nanogrid applications which demands simultaneous ac and dc supply. Operation of the proposed converter is validated by laboratory prototype. NEXYS 4 is used to generate control signals to the switches. Split-Pi converter consists of four switches S1, S2, S3 and S4 as shown in Fig 1. Switches S1 and S2 are boost switches whereas S3 and S4 are buck switches Hybrid Split-Pi is derived from replacing the boost switch S2 of the traditional split pi converter by a single phase Voltage source inverter (VSI) network as shown in Fig 2. The four switches S21, S22, S23 and S24 replace S2 © 2016 IEEE.